2017
DOI: 10.1039/c7ra11086c
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondria-targeting ratiometric fluorescent probe for the detection of hypochlorite based on the FRET strategy

Abstract: In this study, a ratiometric fluorescent probe (IRP) for À OCl was designed based on the fluorescence resonance energy transfer (FRET) platform. The probe was fabricated by integrating an imidazo [1,5-a] pyridine moiety (donor) with a rhodamine moiety (acceptor). We evaluated its properties for recognizing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The result is similar to a previous report. 28 The typical HRTEM image of asprepared GO showed that the GO sheet was about 1 Â 1 mm in size with occasional folds, crinkles and rolled edges (Fig. 1C).…”
Section: Characterization Of Gomentioning
confidence: 95%
“…The result is similar to a previous report. 28 The typical HRTEM image of asprepared GO showed that the GO sheet was about 1 Â 1 mm in size with occasional folds, crinkles and rolled edges (Fig. 1C).…”
Section: Characterization Of Gomentioning
confidence: 95%
“…In general, the donor emission dye must have a strong overlap with the acceptor absorption, which essentially restricts the development of FRET‐based couple systems. To this end, different groups have recently designed and synthesized new impy probes, demonstrating their value for FRET‐based practical applications [11,125,126,131] …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hydrogen ion plays an important role in the entire cell life (tumour growth and corresponding enzymatic and metabolic activity proliferation), at this regards impy probes have been reported as “ on‐off ” pH probe in living cells [10,31] . In this context, different groups have recently designed and synthesized new fluorophores based on impy nucleus, demonstrating their value for ratiometric pH‐sensors based on a dual emission pathway [29,30] and FRET‐based practical applications in biological systems [11,125,126,131] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations